ASEAN Naval Force: The Next Defense Regionalism? - Andromeda Windra Ciptadi (Jurnal Maritim Indonesia (Indonesian Maritime Journal), 2021)
AbstractToday’s intertwined world requires cooperation among countries, including Southeast Asian nations. The two hotspots identified in Southeast Asian waters might bring up common maritime threats. Increasing maritime tensions in the region drive scholars and observers discussing the possibility of the formation of ASEAN naval force to maintain regional stability. However, considering the nature of ASEAN, such initiative is hard to realize, even though contemporary ASEAN adopts what is widely known as the three pillars of the ASEAN community, which one of them is political-security community. Defense pact or any closer defense arrangement would only happen if countries share common security perception. What is need for ASEAN navies is to enhance existing arrangements and further discussion in more applicable SOP for operational units at sea.Keywords: ASEAN Naval Force, Defense Regionalisme, ASEAN Community.